2018
DOI: 10.1002/hep.29773
|View full text |Cite
|
Sign up to set email alerts
|

NACSELD acute‐on‐chronic liver failure (NACSELD‐ACLF) score predicts 30‐day survival in hospitalized patients with cirrhosis

Abstract: Although infection status remains an important predictor of death, NACSELD-ACLF was independently validated in a separate large multinational prospective cohort as a simple, reliable bedside tool to predict 30-day survival in both infected and uninfected patients hospitalized with a diagnosis of cirrhosis. (Hepatology 2018;67:2367-2374).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
230
1
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 219 publications
(247 citation statements)
references
References 34 publications
10
230
1
6
Order By: Relevance
“… ACLF is defined as ≥2 organ failures as per the NACSELD from Bajaj et al (2014) and O’Leary et al (2018). …”
Section: Resultsmentioning
confidence: 99%
“… ACLF is defined as ≥2 organ failures as per the NACSELD from Bajaj et al (2014) and O’Leary et al (2018). …”
Section: Resultsmentioning
confidence: 99%
“…EASL describes them as an acute precipitant among 21% patients with AD and in 30% patients with ACLF . North American Consortium for the Study of Liver Diseases describes them as a precipitant in majority of the patients with ACLF at admission . We have previously shown sepsis or SBP as the commonest acute precipitant in 66% admitted patients with ACLF .…”
Section: Discussionmentioning
confidence: 99%
“…Because infections are one of the most common complications leading to ACLF and delisting, it is imperative that clinicians reduce the risk for infectious complications for patients with cirrhosis . Therefore, it is surprising that more than half of all admitted patients were taking a PPI.…”
Section: Discussionmentioning
confidence: 99%
“…With an increased need for LT and the changes in the patient population listed for transplant, we expect more patients to need hospitalization before transplant . In addition, we anticipate ACLF will also continue to increase in incidence before LT. Current data have shown that transplant‐free survival is markedly reduced in patients who develop ACLF, regardless of the definition of ACLF used . This is also applicable to patients listed for LT who have a high mortality before LT once ACLF develops …”
mentioning
confidence: 91%